The Influence of Organizational Culture, Work Competence and Work Motivation on Organizational Commitment - Yuan Badrianto; Dahlia Permatasari (Privietlab, 2022)
Having human resources who are loyal to the company is an asset that is expected for company owners to establish the company's business progress. To get employees who have a high sense of commitment to the place where they work can be influenced in various ways. One of them is by paying attention to aspects of organizational culture, work competence, and employee motivation. In addition, the commitment instilled in employees is also able to influence in developing the company itself so that employees have a role to play in achieving company goals. This study aims to analyze the influence of organizational culture, work competence and work motivation on organizational commitment at PT Kalbe Farma which causes an increase in employees resigning every month. The type of research used is quantitative research. With a population of employees and sampling with the Probabilty Sampling technique with a sample of 77 respondents. The data obtained from the research sample is in accordance with the statistical data which is then interpreted. Data collection techniques include observation, distributing questionnaires and literature study. The analytical methods used are validity test, reliability test, classical assumption test, multiple linear regression and hypothesis testing through t test, and classical assumption test using SPSS 26 program. The results of the analysis show that organizational culture, work competence and motivation to work together positive and significant effect on organizational commitment. The results of this study concluded that organizational culture, work competence and work motivation had a significant partial and simultaneous effect on PT Kalbe Farma's organizational commitment.